Verification of Point Dose on MU Calculator for Bleeding Cases - Alhamid, Mohammad Zamakhsari; Ramadan, Arief Dian; Wibowo, Wahyu Edy; Anam, Choirul (Journal of Physics and Its Applications, 2025)
Bleeding is a frequent issue among cancer patients, affecting about 6% to 10% of those with advanced-stage cancer. External radiation therapy is a highly effective method for reducing or even stopping bleeding, with success rates ranging from 45% to 100%. In bleeding cases, radiation therapy must be delivered quickly and precisely. To expedite the process, some standard steps in radiation therapy, such as the CT simulation and planning via the treatment planning system (TPS), are often skipped. Consequently, accurate Monitor Unit (MU) calculations are essential to ensure that the dose received by the patient does not deviate by more than 5%, as recommended by the ICRU. Using guidelines from AAPM TG 71, MU calculations were formulated and compiled into a Microsoft Excel worksheet called the MU Calculator. Several key parameters, including dose prescription, output factor (OF), and tissue maximum ratio (TMR), were input into the MU Calculator and verified through point dose verification on a slab phantom using the SAD technique. The verification was conducted using 10 MV energy across various field sizes (10 x 10, 12 x 12, 14 x 14, 16 x 16, 18 x 18, and 20 x 20) cm² at depths of 6, 8, and 10 cm, utilizing a PTW Farmer detector with dose prescriptions of 200, 300, and 400 cGy. The field size, depth, and dose prescription were selected to align with common requirements for bleeding cases. By applying the dose calculation formula recommended by TRS 398, the deviation between the prescribed and measured doses was found to be less than 2.5%. These deviations were attributed to factors such as measurement setup, temperature and pressure conditions, polarity effects, and detector recombination effects. The MU Calculator has been validated, demonstrating compliance with ICRU recommendations, and is thus suitable for use in bleeding cases that demand swift and precise external radiation therapy.